(untitled) (Research, Society and Development, 2021)
The research was carried out with the objective of designing a theoretical conceptual model, which allows to improve budget planning and intra-administrative interoperability of the Graduate School of the National University of Tumbes. The study was of a quantitative approach, descriptive and correlational level; non-experimental cross-sectional design; The sample consisted of 294 collaborators, including managers, administrators and students of the master’s and doctoral programs of the Graduate School of the National University of Tumbes. The survey was used as a technique; The instruments were elaborated in Google forms, they were subjected to validation and reliability, obtaining the Cronbach’s Alpha of 0.938 for the instrument applied to administrative personnel and 0.909 for the instructional applied to students. The data were processed in the Statistical Package for the Social Sciences - SPSS 26, which allowed obtaining information and designing the theoretical conceptual model, to improve budget planning and intra-administrative interoperability of the Graduate School of the National University of Tumbes. Concluding that the a priori theoretical implementation of the model will allow the Graduate School of the National University of Tumbes to include in its Institutional Operational Plan the activities that intra-administrative interoperability requires, achieving with its implementation modernize the institution.